Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of artificial light at night on fishes: A synthesis with future research priorities - Arshpreet Bassi; Oliver P. Love; Steven J. Cooke; Theresa R. Warriner; Christopher M. Harris; Christine L. Madliger (Fish and Fisheries, 2022)
Nearly all organisms rely on natural fluctuations of light as cues for synchronizing physiological processes and behavioural actions associated with foraging, growth, sleep and rest, reproduction, and migration. Consequently, although artificial lighting sources have provided a plethora of benefits for humans, they can lead to disruptions for wild organisms. With one quarter of the human population living within 100 km of coastlines, there is great potential for artificial light at night (ALAN) to influence the physiology, behaviour and fitness of fishes. Through a review of the literature ( n = 584 publications focused on the effects of ALAN on individual organisms or ecosystems), we illustrate that most papers have concentrated on terrestrial species (59%) compared with aquatic species (20%) or a mixed approach (21%). Fishes have been underrepresented in comparison with many other taxa such as birds, insects and mammals, representing the focus of less than 8% of taxa‐specific publications. While the number of publications per year focusing on fishes has generally been increasing since the mid‐2000s, there has been a downturn in publication rate in the last few years. To understand where research related to ALAN in fishes has been focused, we partitioned studies into categories and found that publications have mostly concerned behaviour (41.0%), abundance and community structure (24.4%), and physiology (22.8%), while the longer‐term effects on fitness (6.9%) are lacking. We synthesize the research completed in fishes and outline future priorities that will help ascertain the short‐ and long‐term consequences of this relatively novel stressor for fish health and persistence.

Selecting with markers linked to the PPVres major QTL is not sufficient to predict resistance to Plum Pox Virus (PPV) in apricot - S. Decroocq; A. Chague; P. Lambert; G. Roch; J-M. Audergon; F. Geuna; R. Chiozzotto; D. Bassi; L. Dondini; S. Tartarini; J. Salava; B. Krška; et al. (Tree Genetics & Genomes, 2014)

Radiation hybrid QTL mapping of Tdes2 involved in the first meiotic division of wheat - F. M. Bassi; A. Kumar; Q. Zhang; E. Paux; E. Huttner; A. Kilian; R. Dizon; C. Feuillet; S. S. Xu; S. F. Kianian (Theoretical and Applied Genetics, 2013)

Wheat Zapper: a flexible online tool for colinearity studies in grass genomes - Loai M. Alnemer; Raed I. Seetan; Filippo M. Bassi; Charith Chitraranjan; Adam Helsene; Paul Loree; Steve Bou Goshn; Yong Q. Gu; Ming-Cheng Luo; M. Javed Iqbal; Gerard R. Lazo; Anne M. Denton; et al. (Functional & Integrative Genomics, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

A Zea mays 39-kDa thylakoid transglutaminase catalyses the modification by polyamines of light-harvesting complexII in a light-dependent way - M. Della Mea; A. Di Sandro; L. Dondini; S. Del Duca; F. Vantini; C. Bergamini; R. Bassi; D. Serafini-Fracassini (Planta, 2004)

Occurrence of the lutein-epoxide cycle in mistletoes of the Loranthaceae and Viscaceae - Shizue Matsubara; Tomas Morosinotto; Roberto Bassi; Anna-Luise Christian; Elke Fischer-Schliebs; Ulrich Lttge; Birgit Orthen; Augusto C. Franco; Fabio R. Scarano; Britta Frster; Barry J. Pogson; C. Barry Osmond (Planta, 2003)

Suborganellar localisation and effect of light on Helianthus tuberosus chloroplast transglutaminases and their substrates - L. Dondini; S. Del Duca; L. Dall'Agata; R. Bassi; M. Gastaldelli; M. Della Mea; A. Di Sandro; I. Claparols; D. Serafini-Fracassini (Planta, 2003)

The structure of duplications on human acrocentric chromosome short arms derived by the analysis of 15p - I. Piccini; L. Ballarati; C. Bassi; M. Rocchi; A. Marozzi; E. Ginelli; R. Meneveri (Human Genetics, 2001)

The Soret absorption properties of carotenoids and chlorophylls in antenna complexes of higher plants - Roberta Croce; Gianfelice Cinque; Alfred R. Holzwarth; Roberto Bassi (Photosynthesis Research, 2000)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Generalized cross-covariances and their estimation - H. R. Künsch; A. Papritz; F. Bassi (Mathematical Geosciences, 1997)